Modularisation of vocational training in Germany, Austria and Switzerland : parallels and disparities in a modernisation process - Pilz, Matthias [Verfasser] (My University, 2012)
"This article considers the modularisation of initial vocational training (including apprenticeships) as a modernisation strategy in Germany, Austria and Switzerland. Training systems are similarly structured in these three countries with the apprenticeship system at their heart, and the three national philosophies of education and training are largely comparable. The approach in each country will be outlined and the three will then be compared in terms of the background to modularisation, key drivers and decision-making procedures, and forms and intensity of modularisation. The article concludes that in all three countries, technical and organisational change and greater labour market flexibility are driving the pressure to modularise. While the educational policy players and modalities differ, all three countries have adopted a form of modularisation that is limited in terms of its scope and how radical it is. The article proposes a concept that enables training to be modularised while leaving intact a country’s existing training philosophy and Berufskonzept, a German concept that embodies the extent to which workers internalise an occupational identity." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 2.3 Berufsbildungspolitik; T 1.5 International vergleichende Berufsbildungsforschung; Berufsausbildung; Duales System; Reform; Modularisierung; Beruflichkeit; Internationaler Vergleich; Bundesrepublik Deutschland; Österreich; Schweiz